A semi-solid lithium ion battery pole piece, a preparation method and application thereof

CN122907641APending Publication Date: 2026-10-13SHENZHEN EPT BATTERY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611381592.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,半固态电池在循环过程中仍存在两大核心问题:一是极片活性物质随充放电发生体积胀缩,反复循环后易出现表面裂纹并向内部扩展,导致活性物质粉化、电池容量快速衰减;二是半固态体系中固-液、固-固界面接触不充分,界面阻抗较高,制约了倍率性能与循环寿命的提升

Benefits of technology

(1)本发明的半固态锂离子电池极片在活性物质层中构建双酚-S环氧树脂-巯基化导电剂-氨基MOF的共价交联体系,配套活性酯固化剂与咪唑类促进剂,配合负热膨胀材料与氧化物固体电解质,在保证高能量密度的前提下,显著降低半固态电池的界面阻抗,提升极片尺寸稳定性与循环寿命,同时兼具优异的高温安全性能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to a kind of semi-solid lithium ion battery pole piece and its preparation method and application, the semi-solid lithium ion battery pole piece is built in active material layer Double-bonded phenol-S epoxy resin-mercapto conductive agent-amino MOF's covalent crosslinking system, matching active ester curing agent and imidazole type accelerator, cooperate negative thermal expansion material and oxide solid electrolyte, under the premise of guaranteeing high energy density, significantly reduce the interface impedance of semi-solid battery, improve pole piece dimensional stability and cycle life, simultaneously have excellent high-temperature safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of lithium-ion batteries, specifically to a semi-solid lithium-ion battery electrode, its preparation method, and its application. Background Technology

[0002] Semi-solid-state lithium-ion batteries combine the low interfacial impedance of liquid batteries with the high safety of all-solid-state batteries, making them an important technological direction for next-generation power batteries. However, semi-solid-state batteries still face two major challenges during cycling: First, the active materials on the electrodes expand and contract in volume during charging and discharging, and repeated cycles can easily lead to surface cracks that propagate inward, resulting in pulverization of the active materials and rapid capacity decay. Second, the solid-liquid and solid-solid interfaces in semi-solid systems are not sufficiently contacted, resulting in high interfacial impedance, which restricts the improvement of rate performance and cycle life.

[0003] In existing technologies, negative thermal expansion films are typically applied to the electrode surface to suppress electrode cracking. However, surface modification alone is insufficient to address the issues of thermal stress and volume changes within the electrode bulk phase. Other technologies enhance high-temperature safety by incorporating epoxy resin into the electrode, but these generally lack a suitable curing system. Insufficient cross-linking of the epoxy resin prevents the formation of a stable three-dimensional network, limiting its thermal expansion control effect. Furthermore, ordinary epoxy resins can easily lead to increased electrode impedance. In addition, MOF-type porous materials are often used to improve ion conductivity, but direct addition can cause particle agglomeration and poor compatibility with the organic matrix interface, which can actually increase the electrode's internal resistance. Conventional conductive agents only perform electron conduction and cannot participate in electrode structural reinforcement; they are prone to migration and agglomeration during cycling, damaging the conductive network.

[0004] Therefore, developing a semi-solid-state battery electrode that combines low interfacial impedance, high dimensional stability, and long cycle life is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a semi-solid lithium-ion battery electrode, its preparation method, and its application.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a semi-solid-state lithium-ion battery electrode, comprising a current collector and an active material layer disposed on the surface of the current collector, the active material layer comprising the following raw materials by weight percentage: The composition includes: 80-92% positive electrode active material, 1.0-3.0% bisphenol-S epoxy resin, 2.0-6.0% mercapto-conductive agent, 0.5-2.0% amino MOF, 0.5-2.0% negative thermal expansion material, 0.3-1.5% solid electrolyte, 1.5-5.0% binder, 0.2-0.8% active ester curing agent, and 0.02-0.1% curing accelerator. Wherein, the amino MOF is UIO-66-NH2; The preparation method of the thiolized conductive agent includes the following steps: The conductive agent and solvent are mixed, and (3-mercaptopropyl)trimethoxysilane is added. The pH value is adjusted to 2.9-3.1 to carry out the thiolation reaction, and the reactant is filtered, washed and dried to obtain the thiolated conductive agent.

[0007] This invention utilizes bisphenol-S epoxy resin with a matching active ester curing agent and imidazole accelerator to simultaneously achieve cross-linking and curing at an electrode drying temperature of 80-110℃, constructing a three-dimensional covalent cross-linked network of thiol-epoxy-amino groups. Specifically, the thiol groups on the surface of the thiolized conductive agent undergo deprotonation under the action of the amino group of UIO-66-NH2, generating highly active thiolate anions. These anions then undergo ring-opening reactions with the epoxy groups to form thioether bonds and secondary hydroxyl groups. Simultaneously, the amino group of UIO-66-NH2 itself can directly ring-open bond with the epoxy group, thereby firmly anchoring the conductive agent and MOF particles covalently within the resin network. This cross-linked network restricts the relative displacement of the active material particles at the bulk level, buffering volume expansion and contraction during charge and discharge processes. Combined with the intrinsic properties of nano-negative thermal expansion materials, it jointly counteracts electrode thermal expansion, reduces internal stress, and effectively inhibits the generation and propagation of cracks during cycling.

[0008] Meanwhile, the mercapto-conductive agent not only constructs a continuous electron transport pathway to ensure rate performance, but also avoids migration and aggregation during cycling through covalent anchoring, maintaining the integrity of the conductive network after long cycling; UIO-66-NH2, with its porous structure, assists in lithium-ion transport and adsorption storage of electrolyte, and works with solid electrolyte to optimize ion conduction path and reduce interfacial impedance. Its rigid framework can also further restrict the thermal movement of resin segments, synergistically improving the size stability of the electrode.

[0009] Preferably, the weight ratio of the thiolized conductive agent to the amino MOF is (3-5):1.

[0010] Preferably, the positive electrode active material is at least one of nickel-cobalt-manganese ternary materials, lithium cobalt oxide, lithium iron phosphate, lithium manganese iron phosphate, or lithium manganese oxide.

[0011] Preferably, the negative thermal expansion material is ZrW2O8 and / or ScF3; the particle size of the negative thermal expansion material is 200-300 nm.

[0012] Preferably, the solid electrolyte is a sulfide solid electrolyte, an oxide solid electrolyte, or a phosphate solid electrolyte. More preferably, the solid electrolyte is a NASICON-phase oxide electrolyte material Li7La3Zr2O. 12 .

[0013] Preferably, the adhesive is polyvinylidene fluoride; the curing accelerator is any one or a combination of two of 2-ethyl-4-methylimidazole and 1-cyanoethyl-2-ethyl-4-methylimidazole.

[0014] Specifically, in the preparation method of the thiolized conductive agent, the temperature of the thiolization reaction is 58-62℃ and the time is 5-6h; the material-to-liquid ratio of the conductive agent to the solvent is (2-3)g:(120-180)mL; the solvent is isopropanol and deionized water in a volume ratio of (3-6):1; the weight ratio of the conductive agent to (3-mercaptopropyl)trimethoxysilane is (4-6)1; and the conductive agent is at least one of conductive carbon black, carbon nanotubes, and Ketjen black.

[0015] In a second aspect, the present invention provides a method for preparing the semi-solid lithium-ion battery electrode described in the first aspect, comprising the following steps: (1) Preparation of thiolized conductive agents; (2) Dissolve bisphenol-S epoxy resin, active ester curing agent, and curing accelerator in a solvent, add mercapto-conductive agent, aminated MOF, negative thermal expansion material, and solid electrolyte, and disperse evenly to obtain functional phase slurry; (3) The positive electrode active material is mixed with a portion of the binder to prepare the main slurry, and then the functional phase slurry and the remaining binder are added, and the mixture is stirred and degassed to obtain the positive electrode slurry; (4) The positive electrode slurry is coated on the surface of the current collector, dried in sections and rolled to obtain the semi-solid lithium-ion battery electrode.

[0016] Preferably, the temperature of the segmented drying in step (4) is 80-110℃, and the total drying time is 15-30min.

[0017] Thirdly, the present invention provides a semi-solid lithium-ion battery comprising the semi-solid lithium-ion battery electrode of the first aspect.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The semi-solid lithium-ion battery electrode of the present invention constructs a covalent cross-linking system of bisphenol-S epoxy resin-thiolized conductive agent-amino MOF in the active material layer, and is equipped with active ester curing agent and imidazole accelerator, combined with negative thermal expansion material and oxide solid electrolyte. Under the premise of ensuring high energy density, it significantly reduces the interface impedance of semi-solid battery, improves electrode size stability and cycle life, and also has excellent high temperature safety performance.

[0019] (2) This invention improves electrochemical performance while also ensuring high-temperature safety and high energy density. After curing, the bisphenol-S epoxy resin is insoluble in conventional carbonate electrolytes. When an internal short circuit or abnormal temperature rise occurs in the battery, it can soften, flow, cover, or even thermally decompose to form a barrier layer, cutting off the electrochemical reaction contact and increasing the thermal runaway threshold. Furthermore, the total proportion of all functional components is less than 10%, while the proportion of positive electrode active material can reach over 80%, ensuring the high energy density of the semi-solid-state battery. The preparation process is based on an optimized traditional coating process, adding only a functional phase pre-dispersion step. Crosslinking curing and electrode drying are completed simultaneously, allowing for adaptation to existing production lines without the need for additional large-scale equipment. The segmented drying process ensures stable solvent evaporation and uniform crosslinking of the epoxy resin, avoiding defects such as pinholes and cracks in the electrode, resulting in high product yield and easy large-scale production. Detailed Implementation

[0020] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0021] Unless otherwise specified, all other materials and reagents used in the examples are commercially available.

[0022] Examples 1-5 and Comparative Examples 1-5 The types and sources of raw materials used in Examples 1-5 and Comparative Examples 1-5 are as follows; Positive electrode active material: NCM523 nickel-cobalt-manganese ternary material (battery grade); Bisphenol-S-epoxy resin (BPSER): purchased from Wuhan Kemic Biomedical Technology Co., Ltd., model KMK-1869; Conductive agent: Super P conductive carbon black, battery grade; Amino MOF: UIO-66-NH2, CAS No. 1260119-00-3; UIO-66: CAS No. 1072413-89-8; Negative thermal expansion material: ZrW2O8, particle size 200~300nm, purity ≥99%; Solid electrolyte: Li7La3Zr2O 12 Nanoscale, ionic conductivity ≥10 -4S / cm; Adhesive: Polyvinylidene fluoride (PVDF), purchased from Arkema, France, model HSV900; Reactive ester curing agent: purchased from DISEN, model HPC-8000-65T; Curing accelerator: 2-ethyl-4-methylimidazolium; Silane coupling agent: (3-mercaptopropyl)trimethoxysilane (KH590); Solvent for slurry: N-methylpyrrolidone (NMP, battery grade); Unless otherwise specified, all other materials and reagents used in the examples are commercially available.

[0023] General preparation method Preparation of thiol-modified conductive agents The conductive agent and solvent were mixed at a ratio of 25g:1500mL, ultrasonically dispersed for 35min, KH590 was added, and the pH was adjusted to 3.0 with dilute hydrochloric acid. The mixture was then incubated in a water bath at 60℃ for 5.5h to carry out the thiolization reaction. The reaction product was filtered and washed three times each with 50% ethanol solution and anhydrous ethanol, and then vacuum dried at 60℃ for 12h to obtain the thiolized conductive agent. The solvent was isopropanol and deionized water in a volume ratio of 5:1, and the weight ratio of the conductive agent to (3-mercaptopropyl)trimethoxysilane was 5:1. Preparation of positive electrode sheet (1) Preparation of functional phase paste: Bisphenol-S-epoxy resin, active ester curing agent, and 2-ethyl-4-methylimidazolium were dissolved in NMP according to the proportion and stirred at 50°C until completely dissolved; thiolized conductive agent, UIO-66-NH2, ZrW2O8, and Li7La3Zr2O were added. 12 Disperse at high speed for 30 minutes to obtain a uniform functional phase slurry.

[0024] (2) Mixing of main slurry: Add the positive electrode active material and 1 / 2 of the designed amount of PVDF into NMP and planetary stir for 2 hours until uniform; slowly add the above functional phase slurry and continue stirring for 1 hour; finally add the remaining PVDF, adjust the slurry solid content to 72%, and vacuum degas for 20 minutes to obtain the positive electrode slurry.

[0025] (3) Coating and molding: The positive electrode slurry is uniformly coated on the surface of a 15μm thick aluminum foil current collector. The segmented drying process is adopted: drying at 80℃ for 10min, drying at 100℃ for 5min, and drying at 110℃ for 3min. During the drying process, the epoxy resin crosslinking and curing are completed simultaneously. After drying, the surface density is rolled to 28mg / cm² to obtain a semi-solid lithium-ion battery positive electrode sheet.

[0026] Semi-solid-state battery assembly The above-mentioned positive electrode, artificial graphite negative electrode, and 12μm PP / PE composite separator are assembled into a soft-pack battery cell. A mixture of EC / EMC electrolyte containing 1.0M LiPF6 and methyl methacrylate monomer is injected, and after in-situ polymerization at 55℃ for 3 hours and pressure formation, a semi-solid-state lithium-ion battery with a rated capacity of 1Ah is obtained.

[0027] Example 1 The active material layer in this embodiment comprises the following raw materials by weight percentage: The composition includes: positive electrode active material 88.0%, bisphenol-S-epoxy resin 2.0%, mercapto-modified conductive carbon black 4.0%, UIO-66-NH2 1.2%, ZrW2O8 1.0%, solid electrolyte 0.8%, binder 2.5%, active ester curing agent 0.4%, and 2-ethyl-4-methylimidazolium 0.1%.

[0028] The positive electrode and semi-solid battery are prepared according to the general method described above.

[0029] Example 2 The only difference between this embodiment and Example 1 is that the weight percentage of bisphenol-S-epoxy resin is adjusted to 1.0%, the binder is adjusted to 3.5%, and the remaining components and processes are exactly the same.

[0030] Example 3 The only difference between this embodiment and Embodiment 1 is that the weight percentage of UIO-66-NH2 is 0.5%, the weight percentage of ZrW2O8 is 2.0%, the binder is adjusted to 2.2%, and the remaining components and processes are exactly the same.

[0031] Example 4 The only difference between this embodiment and Embodiment 1 is that mercapto-modified carbon nanotubes are used instead of mercapto-modified conductive carbon black, while the other components and processes are exactly the same.

[0032] Example 5 The only difference between this embodiment and Example 1 is that the weight percentage of mercapto-conductive carbon black is adjusted to 3.5% and UIO-66-NH2 is adjusted to 1.7%.

[0033] Example 6 The only difference between this embodiment and Example 1 is that the weight percentage of mercapto-conductive carbon black is adjusted to 4.4% and UIO-66-NH2 is adjusted to 0.8%.

[0034] Comparative Example 1 The only difference between this comparative example and Example 1 is that unmodified conductive carbon black is used instead of mercaptoized conductive carbon black.

[0035] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that UIO-66 is used instead of UIO-66-NH2.

[0036] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that ZrW2O8 is not added, and the missing amount is made up by positive electrode active material.

[0037] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that bisphenol-S epoxy resin is not added, and the missing amount is made up by positive electrode active material.

[0038] Performance testing methods The batteries of Examples 1-6 and Comparative Examples 1-4 were tested as follows: Room temperature cycling performance: At 25℃, the battery is charged to 4.3V with 1C constant current and constant voltage (cutoff current 0.05C), discharged to 3.0V with 1C constant current, and cycled 500 times. The ratio of the discharge capacity on the 500th cycle to the discharge capacity on the first cycle is calculated, which is the capacity retention rate.

[0039] High-temperature cycling performance: At 45℃, using the same charge and discharge regime as normal temperature cycling, 300 cycles were performed, and the capacity retention rate was calculated.

[0040] Rate performance: Based on the discharge capacity at 0.2C rate, the discharge capacity at 1C and 3C rates was tested, and the corresponding capacity ratio was calculated.

[0041] AC impedance testing: After the first cycle of the battery, the AC impedance (frequency range 10) was tested using an electrochemical workstation. -2 -10 5 (Hz, amplitude 5mV), read the charge transfer impedance Rct.

[0042] Electrode thermal expansion coefficient: The active material layer of the electrode is peeled off from the current collector, and the thermal expansion coefficient in the range of 25~15℃ is tested using a thermomechanical analyzer (TMA).

[0043] Electrode peeling force: After 500 cycles at room temperature, the battery was disassembled, and the positive electrode was cut into 15mm wide samples. The peeling force between the active material layer and the current collector was tested using the 180° peeling method.

[0044] Test Results and Analysis The performance test results of each embodiment and comparative example are shown in Table 1.

[0045] Table 1 Performance test results of each sample Example 1 93.2 90.5 89.7 42.3 21.5 26.2 Example 2 91.7 88.1 88.5 45.1 24.8 24.8 Example 3 92.4 89.7 87.9 47.5 20.1 25.4 Example 4 94.1 91.3 91.8 38.6 22.3 26.7 Example 5 90.8 85.9 85.2 46.7 23.6 23.2 Example 6 88.2 85.1 84.5 49.2 25.2 22.4 Comparative Example 1 84.4 80.6 81.7 61.4 29.1 17.9 Comparative Example 2 86.5 82.2 83.0 54.8 26.4 21.3 Comparative Example 3 83.3 80.7 85.8 48.3 32.9 20.2 Comparative Example 4 79.1 75.3 78.4 68.7 35.6 15.6 As shown in Table 1, and combining the data from Example 1 and Comparative Example 4, it can be seen that in Comparative Example 4, without the addition of bisphenol-S epoxy resin, the electrode cannot form a three-dimensional covalent cross-linked network, the coefficient of thermal expansion increases significantly to 35.6 ppm / ℃, the peel force after cycling is only 892 N / m, and the capacity retention rate after 500 cycles at room temperature is only 82.1%. This may be because the epoxy cross-linked network can bind the active material particles in the bulk phase, buffer the volume expansion and contraction during the charging and discharging process, and inhibit the initiation and propagation of cracks. Therefore, the addition of epoxy resin is the key foundation for improving the structural stability and long cycle life of the electrode.

[0046] Based on the data from Example 1 and Comparative Example 1, it can be seen that Comparative Example 1, due to the use of unmodified ordinary conductive carbon black, resulted in the conductive agent being unable to form covalent bonds with the epoxy matrix. This led to migration and aggregation during cycling, which not only disrupted the continuous conductive network, causing the charge transfer impedance to rise to 61.2 Ω, but also reduced the density of the cross-linked network, significantly decreasing the stability of the electrode structure. This demonstrates that mercapto modification allows the conductive agent to simultaneously assume the dual roles of electron conduction and cross-linking sites, ensuring the integrity of the conductive network under long-term cycling while enhancing the degree of cross-linking in the epoxy system.

[0047] Based on the data from Example 1 and Comparative Example 2, it can be seen that when Comparative Example 2 uses amino-free UIO-66 instead of UIO-66-NH2, on the one hand, the basic catalytic effect of the amino group is lost, the activation energy of the epoxy-thiol crosslinking reaction increases, the degree of crosslinking decreases, the coefficient of thermal expansion of the electrode increases, and the interfacial peeling force decreases. On the other hand, the MOF particles and the epoxy matrix are not covalently bonded, resulting in poor interfacial compatibility, and the lack of an amino-mediated lithium-ion transport pathway leads to increased interfacial impedance and decreased rate performance. This demonstrates that the amino group in UIO-66-NH2 can simultaneously achieve the triple functions of crosslinking catalysis, interfacial compatibility, and ion conduction.

[0048] Based on the data from Example 1 and Comparative Example 3, it can be seen that in Comparative Example 3, without the addition of ZrW2O8, the intrinsic thermal expansion coefficient of the electrode increases to 32.9 ppm / ℃, resulting in greater internal stress caused by volume expansion and contraction during cycling, and faster capacity decay. This indicates that the negative thermal expansion characteristics of ZrW2O8 can synergistically work with the structural binding effect of the epoxy crosslinking network to further improve dimensional stability during high temperatures and cycling.

[0049] Based on the data from Examples 1 and 5-6, it can be seen that the battery's overall performance is optimal when the weight ratio of the thiolized conductive agent to UIO-66-NH2 is within the range of (3-5):1. When the ratio is lower than 3:1, the conductive agent content is insufficient, the electronic conduction pathway is limited, and both rate performance and cycle performance decrease. When the ratio is higher than 5:1, the amino MOF content is insufficient, the cross-linking catalysis and ion conduction effects are weakened, the density of the cross-linked network decreases, the coefficient of thermal expansion increases, and the structural stability deteriorates. Therefore, controlling the weight ratio of the two within the range of (3~5):1 can achieve the best balance between electronic conduction, ion conduction, and structural stability.

[0050] In summary, the semi-solid lithium-ion battery electrode of the present invention constructs a covalent cross-linking system of bisphenol-S epoxy resin-thiolized conductive agent-amino MOF in the active material layer, and is equipped with an active ester curing agent and imidazole accelerator, combined with negative thermal expansion material and oxide solid electrolyte. Under the premise of ensuring high energy density, it significantly reduces the interfacial impedance of semi-solid battery, improves electrode size stability and cycle life, and also has excellent high-temperature safety performance.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A semi-solid-state lithium-ion battery electrode, comprising a current collector and an active material layer disposed on the surface of the current collector, characterized in that, The active material layer comprises the following raw materials by weight percentage: The composition includes: 80-92% positive electrode active material, 1.0-3.0% bisphenol-S epoxy resin, 2.0-6.0% mercapto-conductive agent, 0.5-2.0% amino MOF, 0.5-2.0% negative thermal expansion material, 0.3-1.5% solid electrolyte, 1.5-5.0% binder, 0.2-0.8% active ester curing agent, and 0.02-0.1% curing accelerator. Wherein, the amino MOF is UIO-66-NH2; The preparation method of the thiolized conductive agent includes the following steps: The conductive agent and solvent are mixed, and (3-mercaptopropyl)trimethoxysilane is added. The pH value is adjusted to 2.9-3.1 to carry out the thiolation reaction, and the reactant is filtered, washed and dried to obtain the thiolated conductive agent.

2. The semi-solid lithium-ion battery electrode as described in claim 1, characterized in that, The weight ratio of the thiolized conductive agent to the amino MOF is (3-5):

1.

3. The semi-solid lithium-ion battery electrode as described in claim 1, characterized in that, The positive electrode active material is at least one of nickel-cobalt-manganese ternary materials, lithium cobalt oxide, lithium iron phosphate, lithium manganese iron phosphate, or lithium manganese oxide.

4. The semi-solid lithium-ion battery electrode as described in claim 1, characterized in that, The negative thermal expansion material is ZrW2O8 and / or ScF3; the particle size of the negative thermal expansion material is 200-300 nm.

5. The semi-solid-state lithium-ion battery electrode as described in claim 1, characterized in that, The solid electrolyte is a sulfide solid electrolyte, an oxide solid electrolyte, or a phosphate solid electrolyte.

6. The semi-solid-state lithium-ion battery electrode as described in claim 1, characterized in that, The adhesive is polyvinylidene fluoride; the curing accelerator is any one or a combination of two of 2-ethyl-4-methylimidazole and 1-cyanoethyl-2-ethyl-4-methylimidazole.

7. The semi-solid-state lithium-ion battery electrode as described in claim 1, characterized in that, In the preparation method of the thiolized conductive agent, the temperature of the thiolization reaction is 58-62℃ and the time is 5-6h; the material-to-liquid ratio of the conductive agent to the solvent is (2-3)g:(120-180)mL; the solvent is isopropanol and deionized water in a volume ratio of (3-6):1; the weight ratio of the conductive agent to (3-mercaptopropyl)trimethoxysilane is (4-6)1; the conductive agent is at least one of conductive carbon black, carbon nanotubes, and Ketjen black.

8. A method for preparing a semi-solid-state lithium-ion battery electrode as described in any one of claims 1-7, characterized in that, Includes the following steps: (1) Preparation of thiolized conductive agents; (2) Dissolve bisphenol-S epoxy resin, active ester curing agent, and curing accelerator in a solvent, add mercapto-conductive agent, aminated MOF, negative thermal expansion material, and solid electrolyte, and disperse evenly to obtain functional phase slurry; (3) The positive electrode active material is mixed with a portion of the binder to prepare the main slurry, and then the functional phase slurry and the remaining binder are added, and the mixture is stirred and degassed to obtain the positive electrode slurry; (4) The positive electrode slurry is coated on the surface of the current collector, dried in sections and rolled to obtain the semi-solid lithium-ion battery electrode.

9. The method for preparing a semi-solid lithium-ion battery electrode as described in claim 8, characterized in that, In step (4), the temperature for segmented drying is 80-110℃, and the total drying time is 15-30min.

10. A semi-solid-state lithium-ion battery, characterized in that, The semi-solid lithium-ion battery electrode comprises any one of claims 1-7.